Nomenclature and typification of southern African species of Euphorbia - Bruyns, P.V. (African Biodiversity & Conservation, 2012)
Types have been located for most of the 185 species of Euphorbia L. that are known to occur naturally in southern Africa and also for most of their synonyms. Lectotypes or neotypes are selected where possible for those names for which a holotype cannot be found. The synonymy largely follows previous accounts and reasons are given where new synonymy is proposed. Euphorbia huttonae N.E.Br. is reinstated at the level of species and E. franksiae var. zuluensis A.C.White et al. is raised to the level of species as E. gerstneriana Bruyns, nom. nov. A new name, E. radyeri Bruyns, is provided for the rhizomatous plants previously referred to as E. caerulescens Haw., which is synonymous with E. ledienii A.Berger.